Compliance Audit of Work Instructions on Polaris Welding at Manufacturing Industries - Mardevi Nur Fadilla (Social Sciences Insights Journal, 2023)
This study discusses compliance audits of work instructions on the Welding Polaris process at Manufacturing Industries. This study aims to determine the level of operator compliance with work instructions in the Polaris Welding process. This study uses descriptive methods and data collection through interviews, documentation, observation, and document inspection. The results of this study found discrepancies between work instructions and work practices in the field, namely when loading material was not carried out one by one, and not checking consistently whether the filter cap and baseplate were aligned. In addition, the lack of supervision and strict sanctions by the authorities prevent operators from following work instructions properly. However, overall operator compliance was stated to be very effective with an ICQ tabulation percentage of 86.7%.